PEDAGOGICAL SUPPORT OF THE PROCESS OF SELF-DEVELOPMENT OF FUTURE TEACHERS OF PHYSICAL CULTURE IN THE CONTEXT OF DIGITALIZATION OF HIGHER EDUCATION - Voishcheva E.L. ,; Larina I.B. ,; Nekhoroshikh N.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to scientifically substantiate the organization of pedagogical support for the process of self-development of future physical education teachers in the context of digitalization of higher education. Methods and structure of the study. The basis of the experiment was Bunin Yelets State University (Lipetsk region). The sample consisted of 52 first-year students in the direction of training "Pedagogical education" (preparation profiles: physical education, sports training, life safety). In the course of the study, it was proposed to implement network projects using digital tools as part of the organization of pedagogical support for future physical education teachers. A network project was understood as a project that is carried out by a team using network telecommunications and other resources of the digital educational environment. Results and conclusions. Practice has shown that the use of a network project helped to actively involve students in the discussion of various topics and problems, and their solution did not cause any difficulties for students. Experimental work showed positive results. The criteria for the effectiveness of pedagogical support of self-development of future teachers of physical culture was the involvement of students in project activities, their personal achievements, their demand for “support services”.